Optimal sensor placement for damage detection of bridges subject to ship collision - Guo, Y.L.; Ni, Y.Q.; Chen, S.K. (Structural control and health monitoring, 2017)
Summary Ship collisions threaten the safety of bridges over navigable waterways in modern times. Postcollision damage and condition assessment is thus of significant importance for decision making on whether closure of bridge to traffic is necessary and for planning the consequent bridge strengthening or retrofitting. Online structural health monitoring systems provide a unique approach to monitor bridge responses during ship collisions and detect the structural damage. The damage information contained in the monitoring data, which is critical for damage detection, however, is largely dependent on the sensor layout. In this paper, an optimal sensor placement method targeting postcollision damage detection of bridges is proposed for selecting the optimal sensor set so that the measured data are most informative for damage detection. The sensor configuration is optimized by a multi‐objective optimization algorithm, which simultaneously minimizes the information entropy index for each possible ship‐bridge collision scenario. One advantage of the proposed method is that it can handle the uncertainty of ship collision position. It also guarantees a redundancy of sensors for the most informative regions and leaves a certain freedom to determine the critical elements for monitoring. The proposed method is applicable in practice to determine the sensor placement, prior to field testing, with the intention of identifying postcollision damage. The cable‐stayed Ting Kau bridge in Hong Kong is employed to demonstrate the feasibility and effectiveness of the proposed method.